RED JERINGAU (Acorus sp) AS ANTIBIOTIC SUBSTITUTE ON THE BROILER PERFORMANCES INFECTED WITH Salmonella typhimurium - Y. A., Tribudi; Tohardi, A.; Rohayeti, Y. (Majalah Ilmiah Peternakan; Vol 23 No 2 (2020): Vol. 23 No.2 (2020), 2020)
This study aims to determine the effect of adding red jeringau extract through drinking water on broiler performances. This study used 25 Copp strain-broilers produced by PT. Japfa Comfeed Indonesia, which were maintained since day old chicks until 30 days old. This study used five treatments and five replications. The treatment in this study as of P1: chickens not infected with Salmonella typhimurium and not given red jeringau extract (positive control); P2: chickens infected with Salmonella typhimurium, without the extract red jeringau (negative control); P3: chickens infected with Salmonella typhimurium+ extract red jeringau 0.5 ml/kg body weight; P4: chickens infected with Salmonella typhimurium+red jeringau extract 1ml/kg body weight and P5: chickens infected with Salmonella typhimurium + 0.02% body weight tetracycline antibiotics. The data were analyzed using analysis of variance. The result show that red jeringau extract in drinking water had not significant effect (P>0.05) on feed consumption, body weight gain, and feed conversion in broiler as infected with Salmonella typhimurium. It can be concluded that red jeringau extract at 1 ml/kg body weight can be used as a substitute for antibiotics because has not effect on the body weight gain and feed efficiency.